Analysis of Clinical Features of Kounis Syndrome Induced by Cephalosporin - Fang, Weijin; Song, Liying; Deng, Zhenzhen; Sun, Wei; Li, Zuojun; Wang, Chunjiang (Frontiers in Cardiovascular Medicine, 2022)
Background: Cephalosporins are increasingly encountered as a cause of Kounis syndrome. The purpose of this article is to explore the clinical features of cephalosporin-induced Kounis syndrome, and provide references for diagnosis, prevention, treatment, and prognosis. Methods: We collected cephalosporin-induced Kounis syndrome case reports by searching Chinese and English databases from the establishment of the database to October 31, 2021. Results: A total of 25 patients (17 males and 8 females) were included, with a median age of 61 years (range 33-92). Cephalosporins were administered by oral, intravenous and intramuscular routes. All reactions except for 2 patients occurred within 30 minutes. Fourteen patients experienced chest pain, 19 experienced hypotension,16 had cutaneous reactions,10 had respiratory symptoms, 7 had gastrointestinal symptoms. Thirteen patients had elevated troponin levels, and 8 patients had elevated serum tryptase levels. The electrocardiogram showed ST-segment elevation in 13 patients, depression in 4 patients, elevation and depression in 6 patients. Coronary angiography showed normal in 12 patients and abnormal in 13 patients. Skin prick test was positive for cephalosporin in 3 patients. Twenty-four patients recovered except one death after being given anti-allergic and acute coronary syndrome treatment. Conclusions: Kounis syndrome is a serious adverse reaction of cephalosporin. Clinicians should be aware of the importance of keeping Kounis syndrome in mind in every patient receiving cephalosporin and presenting with an acute chest pain or anaphylactic symptoms.